A Critical Review of Analytical Methods for Quantification of Amphotericin B in Biological Samples and Pharmaceutical Formulations - Marena, Gabriel Davi [UNESP]; Ramos, Matheus Aparecido dos Santos [UNESP]; Bauab, Taís Maria [UNESP]; Chorilli, Marlus [UNESP] (Taylor & Francis, 2020)
Amphotericin B (AmB) is an important antifungal agent available in the clinical practice with the action mechanism related to the inhibition of ergosterol molecule present in the fungal cell wall. Given this, in order to expand AmB knowledge, this review article gathers important information of the AmB physical, chemical, and biological properties. In addition, the main analytical methods for quantifying and determining the AmB were also reported in this review, such as high-performance liquid chromatography (HPLC), liquid chromatography, tandem mass spectrophotometry (LC-MS/MS), immunoenzymatic assay (ELISA), capillary zone electrophoresis (CE) stands out and among others. Based in this review article, the scientific community will have important information to choose the best method for analysis in their scientific or clinical research, providing greater security and reliability in the obtained results.
Keywords: Amphotericin B; antifungal; drug monitoring; HPLC; LC-MS/MS